2023
DOI: 10.3390/cells12131712
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Thrombosis and Liver Fibrosis Progression: Mechanisms and Clinical Applications

Abstract: Fibrosis is an unavoidable consequence of chronic inflammation. Extracellular matrix deposition by fibroblasts, stimulated by multiple pathways, is the first step in the onset of chronic liver disease, and its propagation promotes liver dysfunction. At the same time, chronic liver disease is characterized by alterations in primary and secondary hemostasis but unlike previously thought, these changes are not associated with an increased risk of bleeding complications. In recent years, the role of coagulation im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…The imbalance of vWF/ADAMTS-13 exacerbates the low specificity of vWF proteolysis by ADAMTS-13 in patients with LC [ 16 ]. The expression of thrombogenic ultrahigh-molecular-weight vWF multimers (VWF-HMWMs) is increased in the portal venous endothelium in LC [ 33 ]. Thus, the vWF/ADAMTS-13 imbalance may facilitate a local persistence of vWF-HMWMs but not VWF levels in patients with LC and PVT [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance of vWF/ADAMTS-13 exacerbates the low specificity of vWF proteolysis by ADAMTS-13 in patients with LC [ 16 ]. The expression of thrombogenic ultrahigh-molecular-weight vWF multimers (VWF-HMWMs) is increased in the portal venous endothelium in LC [ 33 ]. Thus, the vWF/ADAMTS-13 imbalance may facilitate a local persistence of vWF-HMWMs but not VWF levels in patients with LC and PVT [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…No recommendation can be made about the use of anticoagulation to prevent PVT in PSVD, and this remains an unmet need [ 66 ]. Currently, whether PVT occurrence leads to the worsening of natural history of chronic liver disease is debated; however, on the other hand, as previously described, growing evidence suggests a direct role of anticoagulants in the prevention of liver fibrosis and parenchymal extinction acting on microthrombosis with a reduction in hepatic decompensation risk [ 107 , 159 , 160 , 161 , 162 , 163 , 164 , 165 ]. Indeed, a study conducted in rats with carbon tetrachloride (CCL4) induced liver damage demonstrated a reduction in fibrosis after low weight molecular heparin (LWMH) administration associated with an improvement in liver regeneration [ 166 ].…”
Section: Discussion and Future Perspectives: The Role Of Anticoagulationmentioning
confidence: 99%
“…In cirrhosis, reduced ADAMTS13 activity leads to the accumulation of ultra-large VWF multimers that paradoxically induce abnormal angiogenesis. 38 Studies suggest VWF processing could be a valuable prognostic marker in advanced chronic liver disease. In cirrhotic patients undergoing transjugular intrahepatic portosystemic shunt procedures, those with PVT had significantly higher VWF antigen levels.…”
Section: Understanding Disease Mechanismsmentioning
confidence: 99%